(untitled) (American Journal of Islam and Society, 2017)
In your hands is another thematic issue of AJISS, one that consists of two main contributions that address the Islamic tradition’s prohibition of the homosexual act. Jonathan A. C. Brown’s essay analyzes the authenticity of pertinent hadith traditions, whereas Mobeen Vaid’s essay explores the Qur’anic perspective. Both articles had their origin in presentations by a number of scholars at a colloquium held at the International Institute of Islamic Thought (IIIT) in Herndon, VA, on November 1-2, 2015. Although an earlier version of Vaid’s essay is available online, its original intent and thematic complementarity with Brown’s essay on hadith merit its inclusion here. Together, they make crucial contributions to the scholarship that has reopened the question of how the Islamic scriptural and jurisprudential traditions view this particular sexual practice. In the same workshop, I presented my reflections on the stakes of the rise of new prohomosexual (or at least neutral) laws and cultural formations for Muslim scholarship as well as politics, which I share in a modified form in this editorial essay. In keeping with this issue’s theme of sexual ethics, we also include David Finn’s critical and extensive evaluation of Aysha Hidayatullah’s important Feminist Edges of the Qur’an (New York: Oxford University Press, 2014) ...